A Stakeholder Approach to the Ethicality of BRIC-firm Managers’ Use of Favors - McCarthy, Daniel J. (Journal of business ethics, 2012)
This article investigates the use of favors by managers of BRIC firms to accomplish business goals, the ethicality of which should be determined by the moral reasoning in these countries rather than from a developed country perspective. We define a favor as an exchange of outcomes between individuals, typically utilizing one’s connections, that is based on a commonly understood cultural tradition, with reciprocity by the receiver typically not being immediate, and its value being less than what would constitute bribery within that cultural context. This exchange normally takes place between and among members of networks, and may involve a network outsider contacted by a network insider on behalf of another insider. We see the giver and receiver of the favor, as well as network insiders and outsiders, as stakeholders. Additionally, society could also be considered to be a stakeholder since the practice of using favors generally inhibits the development of legitimate, strong formal institutions, since the use of favors in emerging economies is rooted in cultural traditions that we view as informal institutions. Furthermore, we assert that the practice of using favors can lead to bribery which harms society as a stakeholder both morally and economically. We posit that BRIC-country managers’ behaviors stem from informal, culturally based practices—jeito in Brazil, blat/sviazi in Russia, jaan-pehchaan in India, and guanxi in China. We utilize institutional theory to explain why favors are relied upon, and ISCT to support the argument that the use of favors in environments like the BRICs is generally considered ethical.